The vegetation of the Cape Hangklip area - Boucher, Charles (Department of Biological Sciences, 2016)
Approximately 11 500 ha of coastal plain and mountain vegetation in the Cape Hangklip area of the South-Western Cape Province of South Africa was studied. The suitability of homogeneity functions and of the association-analysis techniques for the analysis of large areas of the distinctive coastal and fynbos vegetation found in the Mediterranean type of climate in this region were investigated. Data were collected at 150 sampling sites of 10 x 5 metres each, which were randomly located on grid intersections within physiographic-physiognomic units delimited on aerial photographs. Phytosociological techniques were used to arrange the data prior to further analysis using frequency modulated homogeneity functions. A classification of the vegetation into 32 communities is proposed with primary subdivisions into Broad-leaved Scrub and Fynbos. This classification is based on the results of the association-analysis of the data.